Numerical Simulation of Mechanical Properties of Irregular Columnar Jointed Rock Mass - Yan, Long; Xiang, Zhipeng; Xu, Weiya; Wang, Rubin; Ji, Hua (Frontiers in Physics, 2022)
Columnar jointed rock masses (CJRM) are characterized by significant anisotropy. The mechanical properties of CJRM are complicated by the presence of columnar joints. In this paper, based on the Voronoi random graph generation algorithm, the irregular CJRM numerical model is established, in which columns are simulated by solid elements while joints are simulated by contact surface elements. Uniaxial compression tests on irregular CJRM are then conducted by using FLAC3D to investigate the deformation and strength characteristics, slippage rules, and failure modes. Results indicate that irregular CJRM exhibit strong anisotropy under uniaxial compression, and the compressive strength varies with joint angle in a typical U-shape curve. Failure modes can be classified as three categories: splitting failure along loading direction, shear-sliding failure along columnar joint, and combined failure of column fracturing and joint splitting. The failure characteristics are then compared with the experimental results. It demonstrates the effectiveness and reliability of applying numerical simulation to investigations on mechanical properties and failure mechanism of irregular CJRM. The results of this study provide helpful information for the design and construction of the project involving CJRM.